(untitled) (The Pakistan Development Review, 2004)
Exchange rate is a price of traded goods in the world market. To maintain the commodities competitive in the market, exchange rate should be adjusted according to the change in prices. If it is adjusted accordingly, then we say that purchasing power parity (PPP) holds in that country. However, phenomenon of PPP is completely kicked out under floating exchange rate regime in the short run [see for example, Rogoff (1999); Mark and Choi (1997); MacDonald (1999); Obstfeld and Taylor (1997); Coleman (1995); O’Connel (1998) and Michael, et al. (1997)]. Recent statement by the President of the National Bank of Pakistan, that the exchange rate and the interest rate are two faces of the same coin [Bokhari (2004)], shows that the changes in the exchange rate is strongly associated with the changes in the interest rate differential.1 It is also argued that under free float the value of currency is determined by demand and supply of foreign exchange and to control the value of currency using open market operations interest rate is used as the key monetary policy tool. Moreover, deterioration of trade balance leads to deprecation in exchange to make the exports competitive in the market and vice versa.